Comparison of exposure to stress and analysis of ways of coping with stress among freight transport and public transport drivers - Katarzyna Urbańska; Aleksandra Żelazko; Joanna Domagalska; Przemysław Nowak (Nofer Institute of Occupational Medicine, 2016)
Background: Fast progress in a lot of economic sectors has greatly contributed to a growing role of road transportation systems, including freight transport and passenger transport. The job of professional drivers is regarded as extremely hard and dangerous, it is associated with high risk of health loss and even life loss. This profession is also associated with mental burden, the main cause of the absence at work and alarming number of road accidents. The aim of study was to compare exposure to stress, check the level of stress and ways to cope with stress in 2 groups of drivers (N = 187). Material and Methods: The study was carried out among public transport drivers and freight transport drivers. The authors' own questionnaire and 2 psychological tests: Perceived Stress Scale (PSS-10) and Posttraumatic Growth Inventory and Inventory to Measure Coping Strategies with Stress (Mini-COPE) were used as the study tools. Results: The level of stress is high in both groups, mostly due to a similar type of work. Both groups practice similar ways to cope with stress, but active ways predominate. Conclusions: The work of a professional driver is considered as extremely stressful. The level of stress among professional drivers should be under continuous control. Employers should introduce preventive programs and educate employees about some professional ways to cope with stress. Med Pr 2016;67(4):455-466